1989
DOI: 10.1001/archderm.1989.01670140149031
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia burgdorferi and Localized Scleroderma

Abstract: Borrelia burgdorferi and Localized SclerodermaTo the Editor.\p=m-\Abereret al,1 in Austria, have suggested that morphea might be related to Borrelia burgdorferi infection. These authors found antibodies to B burgdorferi in five of ten patients with morphea in one study and eight of 15 patients in another study, which used the enzyme\x=req-\ linked immunosorbent assay.2 Patients and Methods.\p=m-\Wetested for antibodies to B burgdorferi in 17 patients (15 women and two men; mean age, 38.8 years) with a history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…suggested that positive serological findings in these patients with morphoea are probably not causally linked to the pathogenesis of morphoea, but are a sign of high population prevalence of antibodies against B. burgdorferi . 2 The prevalence of borreliosis‐specific antibodies in clinically asymptomatic persons was as high as 13·7% in Bavarian forest workers, 27 and has been found in several reports to be 2–3% in healthy blood donors in Germany 28,29 …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…suggested that positive serological findings in these patients with morphoea are probably not causally linked to the pathogenesis of morphoea, but are a sign of high population prevalence of antibodies against B. burgdorferi . 2 The prevalence of borreliosis‐specific antibodies in clinically asymptomatic persons was as high as 13·7% in Bavarian forest workers, 27 and has been found in several reports to be 2–3% in healthy blood donors in Germany 28,29 …”
Section: Discussionmentioning
confidence: 95%
“… 1 In the following years, serological, immunohistochemical and culture approaches were performed to determine the role of Borrelia burgdorferi in the pathogenesis of morphoea. 2–5 However, conflicting results were obtained. Since 1993, several authors have used the polymerase chain reaction (PCR) to detect B. burgdorferi in lesional skin of patients with morphoea, but the relationship between morphoea and this organism has remained controversial.…”
mentioning
confidence: 99%
“…However, antibodies against B. burgdorferi were found in 2–11% of asymptomatic patients depending on the geographical region. 61 In Europe and Asia, DNA from B. burgdorferi was detected by PCR in lesional skin in 0–100% (17 of 82) of patients with morphoea. In the U.S.A. none of 98 patients was reported to be positive.…”
Section: Discussionmentioning
confidence: 99%
“…In clinically asymptomatic patients, antibodies against B. burgdorferi were found in 2–11% of cases depending on the geographical region. 61 For that reason several authors presume that the positive serologies in patients with morphoea are not causally linked to the pathogenesis of morphoea, but are a sign of a high prevalence of antibodies against B. burgdorferi in the local population.…”
Section: Serological Findingsmentioning
confidence: 99%
“…Cases have been reported of patients with localized seleroderma and ESA who have high antibody titres in serum and cerebrospinal fluid, as well as neurological symptoms [18,22]. Other researchers, however, have not eonfirmcd the positive results in serologieal testing [2,[40][41][42] and have attributed the positive results to geographical faetors, wherever the disease is endemic [42].…”
Section: Discussionmentioning
confidence: 99%